Strategi Komunikasi Digital melalui Retorika Visual pada Desain Feeds Instagram @storyblast.id - Rafli Dwi Prasetya; Sutisna Riyanto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The rapid growth of social media, particularly Instagram, has transformed visual content into a pivotal element of digital communication strategies. Instagram’s ability to convey messages quickly, persuasively, and with clarity makes visual design an essential tool in this domain. Visual content serves not only an aesthetic function but also plays a critical role in building credibility, establishing emotional connections, and ensuring message clarity. This study explores the application of digital communication strategies through the lens of visual rhetoric in the Instagram feed designs of @storyblast.id, a Public Relations educational account. Employing a qualitative descriptive approach, the research involved active participation from the researcher, as well as observation, interviews, and a literature review. The findings reveal that effective communication with the audience is achieved when visual rhetoric is implemented systematically. By integrating the principles of ethos, pathos, and logos within the AIDA framework, the Instagram feed enhances trust, evokes emotional responses, and guides understanding in a coherent and rational manner. The study highlights how structured visual rhetoric can significantly improve digital communication outcomes.